2009
DOI: 10.1007/s11145-009-9216-4
|View full text |Cite
|
Sign up to set email alerts
|

Roles of position, stress, and proficiency in L2 children’s spelling: A developmental perspective

Abstract: This study investigated the roles of phoneme position, stress, and proficiency in L2 spelling development by Taiwanese students learning English as a Foreign Language (EFL), an alphabetic writing system typologically different from the learners' L1 logographic system. Structured nonword spelling tests were administered to EFL sixth-graders with lower and higher English proficiency level. The results showed that overall, final phonemes were spelled more poorly than their initial and medial counterparts; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Taiwanese Mandarin-speaking children seemed to experience great diffi culties in grasping the linguistic patterns of English to apply grapheme-phoneme correspondence rules. The inconsistent grapheme-phoneme correspondence in English makes it even more diffi cult for non-alphabetic learners of English to apply alphabetic principles ( Hu, 2000 ;He & Wang, 2009 ;Hong & Chen, 2011 ). After the intervention, both groups had signifi cant improvements in their immediate post-test English word reading in comparison with the pre-test.…”
Section: Discussionmentioning
confidence: 99%
“…Taiwanese Mandarin-speaking children seemed to experience great diffi culties in grasping the linguistic patterns of English to apply grapheme-phoneme correspondence rules. The inconsistent grapheme-phoneme correspondence in English makes it even more diffi cult for non-alphabetic learners of English to apply alphabetic principles ( Hu, 2000 ;He & Wang, 2009 ;Hong & Chen, 2011 ). After the intervention, both groups had signifi cant improvements in their immediate post-test English word reading in comparison with the pre-test.…”
Section: Discussionmentioning
confidence: 99%
“…Children's spelling errors, when examined across multiple dimensions (e.g., phonological, orthographic, morphological, etc. ), provide a dynamic marker of the construction of MGRs and can elucidate particular strategies they may be drawing on to spell (Hong & Chen, 2011). These strategies may be different between first language (L1) and second language (L2) learners.…”
Section: Error Analyses and The Cognitive Or Linguistic Influences On...mentioning
confidence: 99%
“…Yeong and Rickard Liow (2011) suggested that while error analysis is labour-intensive, it affords Canadian Journal of Applied Linguistics : 24, 3 (2021): 79-97 several advantages over conventional accuracy only metrics including: (1) sensitivity to individual differences; (2) finer-grained analyses of cognitive-linguistic processing among linguistically diverse children, and (3) capturing spelling as a multidimensional developmental construct. Indeed, spelling error analyses reflect a valuable methodology to derive insight about oral-to-written connections at the lexical, sublexical, and supralexical levels (Hong & Chen, 2011). Of the studies that have been conducted, cross-linguistic (L1 influences on L2) comparisons have been prominent (e.g., Bahr et al, 2015;Fashola et al, 1996;Wang & Geva, 2003) as have comparisons on the use of linguistic conventions such as the use of vowels (e.g., Hong & Chen, 2011;Wade-Woolley & Siegel, 1997).…”
Section: Spelling Error Analysismentioning
confidence: 99%
See 1 more Smart Citation